Mirror-gazing-induced dissociation impairs self-reported and implicit sense of agency: A causal investigation of dissociation and agency under controlled laboratory conditions - Noa Bregman-Hai; Nirit Soffer-Dudek (PLoS ONE, 2026)
Dissociation and sense of agency disruptions are related, but the causal pattern between them is unknown. This two-phase study explored whether laboratory-induced dissociative experiences impair the sense of agency. Study 1 tested the feasibility of generating dissociation and investigated its effect on explicit (self-reported) agency. N = 98 undergraduate students underwent one of two mirror-gazing manipulation conditions (with or without a suggestive cue) or a control condition (video watching). Mirror-gazing induced dissociation and decreased agency, especially among high trait dissociators, but the control condition was not sufficiently differentiated, as it also increased absorption, a construct which is considered a part of the domain of dissociative experiences. In Study 2, N = 199 undergraduates underwent the same manipulations with an additional improved control condition (article reading) and performed a task assessing agency implicitly. Mirror-gazing impaired explicit agency only among those high in self-reported trait dissociation, whereas it impaired implicit agency generally, perhaps bypassing self-report bias. Reading proved to be a better control condition for dissociation induction. The findings provide pioneering evidence of the causal relationship between dissociation and impairments of the sense of agency. Clinical implications are discussed.